Pedagogical digital literacy - Patrício, Maria Raquel (2018)
Digital literacy is regarded as a core competence in society and schools it is therefore considered to be an essential part of pre-service and in-service teacher education. Future teachers need experience best practices in the pedagogical use of ICT in their initial teacher education programme. Innovative practical courses are required to meet the needs and concerns of the student teachers. Develop programmes according to best practice as informed by evidence-based research, for instance, TPACK framework and the DigCompEDU framework, it’s important for rethink how to integrate the pedagogical use of ICT in initial teacher education. The implementation of pedagogical digital competence in initial teacher education is a priority in my practices and course unit - Information and Communication Technologies in Education (ICTE). ICTE programme enables the student teachers to learn, conduct research and practice with their peers by actively practicing in collaborative teams, centered in the pedagogical use of ICT.